Direct composite restorations on permanent teeth in the anterior and posterior region - an evidence-based clinical practice guideline - part 2: recommendations for composite processing - Sekundo, Caroline; Frese, Cornelia; Frankenberger, Roland; Haak, Rainer; Braun, Andreas; Kraemer, Norbert; Krast, Gabriel; Schwendicke, Falk; Kosan, Esra; Langowski, Eva; Wolff, Diana (The journal of adhesive dentistry, 2024)
Purpose: Part 2 of this German S3 clinical practice guideline provides recommendations for the process of manufacturing composite restorations. It covers key aspects like caries removal, field isolation, matrix and adhesive techniques, as well as light curing and polishing. The outcomes of interest include survival rates and restoration quality. Materials and Methods: A systematic literature search was conducted by two methodologists using MEDLINE and the Cochrane Library via the OVID platform, including studies up to December 2021. Additionally, the reference lists of relevant manuscripts were manually reviewed. Six PICO questions were developed to guide the search. Consensus-based recommendations were formulated by a panel of dental professionals from 20 national societies and organizations based on the collected evidence and ex-pert opinion. Results: The guideline advocates for one-stage selective caries removal near the pulp and underscores the effectiveness of various isolation techniques, adhesive systems, and the crucial role of light polymerization. The use of anatomically pre-formed sectional matrices and phosphoric acid etching is recommended to enhance restoration quality. Additionally, polishing composite restorations is advised to improve surface finish. Conclusion: This guideline provides comprehensive recommendations that inform clinicians on optimizing the composite restoration manufacturing processes. The adoption of these best practices can improve the quality and longevity of dental restorations.
Online veröffentlicht: 17. September 2024
Gesehen am 16.04.2025